Pretreatment Cancer-Related Cognitive Impairment in Hodgkin Lymphoma Patients - Juríčková, Veronika; Fayette, Dan; Jonáš, Juraj; Fajnerová, Iveta; Kozák, Tomáš; Horáček, Jiří (Current oncology, 2023)
BACKGROUND: Cancer-related cognitive impairment (CRCI) is one of the most serious side effects of cancer that negatively impacts the quality of life of cancer patients and survivors. There is evidence of CRCI in Hodgkin lymphoma patients (HL); however, there is a lack of studies examining the presence of cognitive deficits before starting any treatment in HL patients. METHODS: Forty adult patients (N = 40) newly diagnosed with HL (with no previous cancer diagnoses) and 40 healthy controls (N = 40) matched for age, sex, education, and premorbid intellect completed the neuropsychological battery and subjective and objective measures of affective distress and quality of life. RESULTS: The results showed impairment in three out of six cognitive domains: verbal memory and learning, speed of processing/psychomotor speed, and abstraction/executive functions in the HL patients before the initiation of any treatment. The speed of processing/psychomotor speed domain is negatively correlated with depression. CONCLUSION: Cognitive deterioration in verbal memory and learning and abstraction/executive functions domains in HL patients seems to occur before the initiation of treatment independently of anxiety, depression, or physical symptoms. This suggests that HL itself may cause cognitive deficits in these cognitive domains. However, the underlying causes of CRCI still remain unclear.
Keywords: Executive Function; kognice; Hodgkinova nemoc; Cognitive Dysfunction; dospělí; Humans; Adult; lidé; Hodgkin Disease; Quality of Life; exekutivní funkce; Cognition; kvalita života; kognitivní dysfunkce